Analisis Aerodinamis Pada Mobil Hemat Energi Asykar Proto Unri Tipe Prototype Dengan Menggunakan CFD (Computational Fluid Dynamics) - Toni Hendrike; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Aerodynamic has a major influence on vehicles moving at a certain speed. Aerodynamics is influenced by the form factor and air flow that comes in contact directly on the surface of the vehicle, causing obstacles and flow separations that occur in the rear of the vehicle that affect the stability of the vehicle. Obstacles that occur significantly affect vehicle fuel consumption. Thus the purpose of this final project is to simulate coefficient drag and coefficient lift that happened to the Asykar Proto UNRI car using CFD (Computational Fluid Dynamics). Analysis is done to find out the size coefficient drag and coefficient lift and the flow form that works on the Asykar Proto UNRI car with a maximum speed of 80 Km/h. The body shape of the car is designed using software Inventor 2017 then exported to ANSYS 16.0 to do summulation. The research results obtained are magnitude coefficient drag and coefficient lift which works on Asykar Proto UNRI cars which are 1.5 and 0.032. Refers to the result obtained by the experiment changing the shape of the front and windshield the value is large of coefficient drag and coefficient lift decreased to 0.15 and 0.0030. This is because the body on the front and the windshield of the part is the body part of the car that determines the amount of drag. Whereas value coefficient lift on the car Asykar Proto UNRI itself does not affect the stability of the car (lift force) when it runs at a speed of 80Km/h.Keywords: aerodynamics, coefficient drag, coefficient lift, Iventor 2017, ANSYS 16.0.